Contemporary Strategic Innovations in the Indian Medical Industry – a Descriptive Approach to Problem - Chrisidu-Budnik, Agnieszka; Sus, Aleksandra (University of Wroclaw. Faculty of Law, Administration & Economics, 2014)
This article explores the issue of innovation in the medical industry. The main aim was to identify and analyze the character of innovations that are being implemented in this industry. The case study method was used in the analysis. The study focuses on Devi Shetty, i.e. the Indian cardiac surgeon who is renowned for making cutting-edge medical care affordable to the masses. It is especially important that the costs of health care be reduced in India, where more than two-thirds of the population live on less than two dollars a day, but Shetty’s strategies may also be of use in developed countries which are facing the problem of how to finance medical services.Design/methodology/approach: This article presents a case study of Devi Shetty’s chain of clinics, based on which the cause-and-effect relationships between particular kinds of strategic innovations in an innovation pyramid are explained.Findings: This article presents topics related to strategic innovations based on the private health care system in India. Such innovations make it possible to solve the problem of how to provide inexpensive medical services of decent quality to impoverished people, who predominate in this country. Implementation of these innovations involves changing conventional ways of thinking, thus leading to the provision of world-class medical services, establishment of a new (lower) price level and ensures replicability of the model as well as universal access to medical services.Research limitations/implications: The research methodology that was applied in the present study was based on the case study method. The case analyzed here is unique on a global scale and the aim of this study is not to develop a theory, but rather to present a specific individual and this person’s innovative activity in the medical industry. The research method involved analyzing content obtained from various media, including literature on the subject and from the Internet, and it focused on answering the following question: what specific activities has Dr. Devi Shetty undertaken in relation to managing a chain of private clinics which now allow us to discuss certain innovation patterns? Triangulation was not used in this study because it was not possible to employ various data collection and analysis methods in order to improve the comparative assessment of data. Such studies definitely cannot be considered coherent or reliable, but they can be regarded as exploratory research, which can serve as a basis for carrying out explanatory research.Originality/value: This article presents a strategic innovation pyramid, which was created based on the author’s conceptual reflections. The article shows the practical application of this pyramid as well as its implications for activities carried out by both public and business organizations. Also, the concept of “innovation saturation” is introduced. The interdisciplinary character of this approach adds additional value to this article.
Keywords: innowacje; usługi medyczne; opieka zdrowotna; zarządzanie